O CORPO COMO EXPRESSÃO DA CULTURA: Uma proposta de intervenção pedagógica interdisciplinar - TUGEIRO, Lúcia Tereza Pinto (2024)
The research deals with the intermediation of corporeality in interdisciplinary dialogues with the curricular components of Art, Physical Education and Portuguese Language in the 3rd grade of secondary school, originating from concerns about the fragmentation and devaluation that still exists between knowledge and conceptions of the body in education. The issue addressed was to find out how the body as an expression of culture could promote the articulation of curricular disciplines through an interdisciplinary interventional project. In this context, the aim was to investigate the body as an expression of culture in order to promote articulation between the curricular disciplines involved, through an interdisciplinary interventional project with three high school teachers from a state public school in São Luís-MA. The study is qualitative, of the pedagogical intervention type, with a cultural-historical approach. For data collection, semi-structured interviews were conducted with teachers and school management before the intervention, and afterwards with the teachers. Participant observations were also carried out before and during the intervention. The information was processed through the description and explanation of Bogdan and Biklen's (1994) qualitative analysis and interpretation, represented by tables of responses in dialogue with theorists who provided support for the understanding of the body, expression and culture; in the understanding of interdisciplinarity; in the dialogue with teacher training and knowledge; in the reflection on cultural-historical theory, pedagogical intervention and curriculum. The research showed how the body as an expression of culture, based on the unveiling and deepening of didactic-pedagogical strategies experienced by the participating teachers in an interdisciplinary interventional path, with collective, critical reflective and conscious dialogical interlocutions, has great potential in the articulation of interdisciplinary dialogues and in the acquisition of knowledge, the relevance of which lies in the continuous stimulation of integrative and participatory educational environments with a vision of totality and mediating diversity of the body, which is not the property of specific curricular knowledge and much less a mere artifact in teaching learning processes.